NEW RECORD OF GONAD-INFECTING SPECIES OF PHILOMETRA COSTA, 1845 (NEMATODA: PHILOMETRIDAE) FROM HYPORHAMPHUS NAOS BANFORD & COLLETTE, 2001 (HEMIRAMPHIDAE: BELONIFORMES) IN SINALOA, MEXICO - Rivera-Toscano, Diego (2022)
The objective of this work was to identify the species of parasitic nematodes that infect the gonads of female “birdfish” Hyporhamphus naos Banford & Collette, 2001 (Hemiramphidae: Beloniformes). This species of fish is considered key in terms of the local artisanal fishery index, it is economically transcendental for fishermen and regional consumers who annually wait for its arrival in the bay to be consumed. The nematode Philometra Costa, 1845 (Nematoda: Philometridae) was identified parasitizing the female gonads of H. naos. Two immature female nematodes were found (prevalence 8%, mean abundance 0.08 and mean intensity 1). New information is recorded on the distribution of parasitic nematodes of this genus in this area of ​​the tropical Pacific and a new host. This is the first record of Philometra parasitic on female gonads in H. naos fish in Mexico. The first world record was Philometra longa Moravec, Barton & Shamsi, 2021 in the fish Hyporhamphus australis (Steindachner, 1866) and P. inconveniens Moravec, Barton & Shamsi, 2021 in the fish Hyporhamphus melanochir (Valenciennes, 1847) in Australia. The present study extends the knowledge of the composition by species of the Philometrids that parasitize marine fish. The results of this work contribute to the knowledge on the biology, biodiversity and host preference of these parasites in this fish with great regionalization in the consumption of fish species that present a broad gastronomic social identity in these coastal areas in the port of Mazatlan.